Layanan Bimbingan dan Konseling Bagi Siswa Berkebutuhan Khusus pada Sekolah Inklusif - Rahadian Sakti; Budi Susetyo (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2023)
This research aims to determine guidance and counseling services for students with special needs at one of the schools providing inclusive education in the city of Bandung. The research method used in this research is a qualitative descriptive method with data collection techniques through observation and interviews. This research method is used to search for in-depth information. The subject of this research is one of the schools providing inclusive education in the city of Bandung. The results of this research show that guidance and counseling services for students with special needs in inclusive schools are not yet effective. This is caused by the lack of professional guidance and counseling teachers in handling students with special needs and the absence of professional teachers in handling students with special needs. The problems faced include a lack of professional guidance and counseling teachers in dealing with students with special needs and a lack of socialization in dealing with students with special needs. This research was carried out with the hope of measuring the effectiveness of guidance and counseling services for students with special needs and what aspects and efforts need to be improved.